A clinical case of a floating thrombus in the right atrial cavity against the background of massive bilateral pulmonary embolism - D.V. Dobrianskyi; M.S. Abu Abud; D.O. Aloshyna; P.F. Dudka; I.P. Tarchenko; T.V. Mykhailevska; O.Ia. Paraguz (Civic Union "Communicable Diseases Intensive Care Association", 2024)
ABSTRACT. The article presents a clinical case of massive bilateral pulmonary embolism (PE), which was promptly suspected and diagnosed using echocardiography. During the echocardiography, a floating thrombus about 5 cm long and pulmonary hypertension were found in the right chambers of the heart. The patient was urgently referred for a computed tomography scan of the chest organs, where signs of massive PE were detected and he was referred to the intensive care unit for thrombolytic therapy. Due to the correct diagnosis and adequate therapy, the patient managed to save his life. The purpose of our work is to draw the attention of practical doctors to the nonspecific symptoms of PE and the importance of timely diagnosis in the case of an emergency patient.